NARRATIVES ON FOLK HEALING IN BATO, CAMARINES SUR - Mark Philip C Paderan (Universitas Ahmad Dahlan, 2016)
This study on indigenous healing practices because of the interesting fact that despite the presence of medical advancement, there are still people who have the tendency to consult first a folk healer before seeking the help of modern medical practitioners. And what makes it more interesting is that even professionals seek for the help of folk healers. We may have choices on whom to seek and where to go when we have physical ailments but in this age of modern technology, why such healing tradition continues to exist and co-exist with modern medicine remains a baffling question.But these questions were given answers through this research which aimed at probing into the narratives of the healers and their patients on the curative properties and healing remedies of an age-old tradition. Thus, this is a humble endeavor to sustain the perpetuation of Bicol culture and tradition focusing on the stories on folk healing traditions in order to record, preserve and understand the functions in the society of these indigenous age-old healing practices that are struggling to survive yet undeniably at the brink of extinction.The study focused on the collection, translation, and analysis of folk healing narratives in the selected barangays of Bato, Camarines Sur. The study would like to answer the following questions: (1) What types of indigenous healing practices are evident in the narratives? (2) What do these narratives relate in terms of: (a) Abstract/summary; (b) Orientation in terms of time, place, person, situation; (c) Complicating action; (d) Evaluation; (e) Resolution/Result. (3) What roles in the community do these folk healing narratives reveal? (4) What educational material could be produced to preserve and showcase these indigenous healing practices? With regard to the scope of the study, it focused on narratives on traditional healing in the barangays of Bato, Camarines Sur namely; Divina Pastora, Tres Reyes and Santa Cruz being the most densely populated barangays in the roadside of Bato, Camarines Sur. The study gave emphasis on the first-hand information based on the personal experiences of the key informants who will be composed of the healers and their patients. It delimited itself to the collection, translation, and analysis of the narratives on folk healing practices and not mainly on the rituals and processes involve in healing. Further, this study has the intention to benefit some sectors of the society such as the people of Bato; the Local Government Unit of Bato, Camarines Sur; Camarines Sur itself; students who are taking English, Literature and Social Sciences; medical practitioners, the folk healers themselves and future researchers who would like to undergo a study of the same kind and to the researcher himself.